Case report Cutaneous-limited Degos disease – benign variant or distinctive clinical entity? - Szczerkowska-Dobosz, Aneta; Lange, Magdalena; Roszkiewicz, Jadwiga; Sobjanek, Michał; Biernat, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Degos disease is a very rare disorder of unknown aetiology. Pathognomonic cutaneous lesions are frequently complicated by systemic involvement that confers poor prognosis to the patient. Recently, more reports have been published on Degos disease with benign course and less unfavourable prognosis. We report another case of a young female patient presenting a cutaneous form of the disease with a nine-year course, which raises the question of whether systemic and benign, confined to the skin form of Degos disease represent two distinct entities or variants of one vascular disease.